Development and Validation of the Social Anomie Brief Scale (SAS10) Against the New Standards Implemented During the COVID-19 Pandemic - Vilca, Lindsey W. (2022)
“Currently, social anomie is a public health problem worldwide since people show behavior that does not conform to the newly established norms. Faced with this, the aim of the study was to develop and validate the psychometric properties of a short scale to assess social anomie in a sample of 406 adults (48% male and 52% female) between the ages of 18 and 62. Validity was evaluated based on internal structure through confirmatory factor analysis (CFA) and reliability through the internal consistency method with the hierarchical omega coefficient. The results indicate that a bi-factor model presents better indexes of adjustment to the data (χ2=62.86; df=25; p=.000; RMSEA=.061 [IC90% .042-.080]; SRMR=.024; CFI=.99; TLI=.99). Furthermore, the bi-factor model presents adequate levels of reliability for the general factor (ωH=.70) and for the affective (ωhs=.32) and behavior (ωhs=.41) dimensions. In conclusion, the study results provide a conceptual and statistical basis for the psychometric development of the SAS-10 scale in subsequent studies.“